(untitled) (Materiali di Estetica. Terza serie, 2017)
Transition, soundscape, blurring contours: these narratives instruments make see under an individual perspective the story of Tarkovskij’s Stalker. In this paper we analyze, under s stylistical point of view, the opening of first scenes of the movie, and the transitions from vision to sound in Zone’s revelation.